Electrochemical Aptasensor Based on ZnO Modified Gold Electrode. Issue 8 (23rd July 2013) - Evtugyn, Gennady; Cherkina, Uljana; Porfireva, Anna; Danzberger, Jürgen; Ebner, Andreas; Hianik, Tibor
Abstract We developed an electrochemical thrombin aptasensor based on ZnO nanorods functionalized by electrostatically adsorption of 30‐mer DNA aptamers. The sensor surface was characterized by AFM and SEM. The surface layer assembling was optimized using cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) with ferricyanide ions as redox markers. The peak current of the ferricyanide and the charge transfer resistance gradually decreased with increasing concentration of thrombin in the range from 3 pM to 100 nM due to formation of aptamer‐thrombin complexes and slower diffusion of the marker ions through the surface layer. At optimal conditions, a limit of detection (LOD) of 3 pM for EIS measurements and 10 pM for CV response was calculated from the S/N=3.